Snake Venom Metalloproteinases - José María Gutiérrez (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This special edition of Toxins will cover recent developments in snake venom metalloproteinase structure, function and clinical implications. It will include a historical retrospective of the discovery of Snake Venom Metalloproteinases (SVMPs) and early insights into their biochemical mechanisms and how they function in envenomation. The individual articles will review • SVMP Structure • Pathologies associated with SVMPs activities • Mechanism of action; evolution and orthologs • SVMP processing and disintegrins • Potential clinical applications of SVMP scaffolds